Their eyes were watching God - Zora Neale Hurston (Harper and Row, 1990)
The book tells with haunting sympathy and piercing immediacy the story of Janie Crawford's evolving selfhood through three marriages. Fair-skinned, long-haired, dreamy as a child, Janie grows up expecting better treatment than she gets until she meets Tea Cake, a younger man who engages her heart and spirit in equal measure and gives her the chance to enjoy life without being one man's mule or another man's adornment